Physical activity, dietary patterns, and uric acid among menopausal women living on the mountainside - Pratiwi, Retno Anggita; Subrata, Sumarno Adi (Innovation in Health for Society, 2025)
High-altitude environments can impact uric acid levels due to factors like lower oxygen levels, dietary habits, and lifestyle changes. This phenomenon made it essential to investigate these dynamics in mountainous regions. Women living on mountainsides may have unique risk factors for hyperuricemia and related health issues. However, studies on this topic were limited in the literature. This study aimed to investigate the relationship between physical activity, dietary patterns, and blood uric acid levels in menopausal women. Employing a descriptive analytic approach with a correlational design, data was collected using a cross-sectional method from a sample of 60 women living on the mountainside in Temanggung, Central Java, Indonesia. The collected data was analysed using multiple linear regression and chi-square tests. The multiple linear regression analysis, examining physical activity and dietary patterns in relation to blood uric acid levels obtained a statistically significant (p<0.05). This finding indicates a significant relationship between both physical activity and dietary patterns and blood uric acid levels in among menopausal women. Community healthcare workers need to pay particular attention to those living on the mountainside, as these residents are often geographically distant from essential healthcare facilities. Keywords: Community health, dietary patterns, menopausal women, mountainside population, physical activity, uric acid